Changes in immune cell signatures during early infection reflect decoupling of capillary perfusion and glycocalyx dimensions - Hunkemöller, Anna; Wirth, Timo; Rovas, Alexandros; Pavenstädt, Hermann; Klotz, Luisa; Kümpers, Philipp (Frontiers in Immunology, 2025)
IntroductionMicrovascular injury is central to the pathophysiology of sepsis, but its interaction with the immune system in early infection is unclear. This study aimed to phenotype peripheral blood mononuclear cells (PBMC) from emergency department (ED) patients with suspected bacterial infection and correlate the results with microvascular changes.MethodsThis prospective observational study included 49 adult ED patients with suspected infection and 17 healthy controls. Capillary density and glycocalyx dimensions were measured by sublingual microscopy, while peripheral blood immune cell subsets were analyzed by deep flow cytometry.ResultsNetwork visualization of 72 diIerentially regulated parameters revealed specific changes in diIerent immune cell subsets. Innate immune changes included a functional diversion of monocytes towards pathogen defense and tissue repair, whereas adaptive immune changes included the development of CD4+ T cells with Th2-profile and cytotoxic CD8+ T cells. Unsupervised clustering revealed two distinct immune endotypes: E1 with a suppressed immune response and higher disease severity, and E2 with an enhanced immune response and lower disease severity. Patients showed significant reductions in capillary density and glycocalyx dimensions, which were neither correlated in magnitude nor associated with endotypes. There was a strong association between damaged glycocalyx and several monocyte and T-cell subsets. This association was not observed for capillary density.DiscussionWe demonstrate that glycocalyx damage is associated with a unique immunological signature, distinct from functional capillary density. These findings provide a strong basis for future studies of immune dysregulation and microvascular dysfunction in infection.